Estudo microclimático de recortes urbanos vegetados em Belo Horizonte - MG, através de modelagem micrometeorológica - Camila Araujo de Sirqueira (2014)
This work consists of a microclimatic analysis of three sections located at the Pampulha region, concerning the influence of vegetation in this inhabited urban microclimate, as a way of preventing hypothetical scenarios regarding its presence or absence. This assessment began from an analysis of the urban configuration and microclimatic consequences of the interference of vegetation and native groundcovering on urban spaces, by observing ground cover material, such as concrete and asphalt, and vegetation, like true grass and trees up to 20 meters tall. As a way of characterizing the areas studied at the Pampulha region for their urban aspects, thermal conditions resulting from spatial configuration (occupancy) were rated through in loco measurements and computer software, predicting possible microclimatic modifications of the areas in question. The performance of a quantitative analysis on the temperature conditions, relative humidity, groundcovering radiation temperatures, of both the present situation and thermal and dynamic effects predicted from future vegetation modifications were done using software simulation by ENVI-met®. The software is sensitive to vegetation changes in height and configuration, treetop density and the humidity generated by the evapotranspiration of leafs, as well as the absence of those in urban areas. The results made possible distinguish ground cover by vegetal groundcovering as well as industrialized materials, as there is a significant variation in the microclimate, demonstrating that the choice of cover material and the presence of vegetation is fundamental in the characterization of an urban area and its environment, as both are influenced by alterations of these elements. Therefore, it is important to understand this connection between urban microclimate, materials used, native vegetation and sustainability, which demands harmony between all social, economic and environment factors.